Maturity and spawning of Osteobrama bakeri (Day) - a threatened - Euphrasia, C J; Madhusoodana Kurup, B (Indian Journal of Fisheries, 2011)
Maturity and spawning of Osteobrama bakeri were studied during June 2001 to May 2003. O. bakeri of Periyar River breeds twice in a year, during April-June and October-November. Ripe males and gravid females were observed from September to November and February to June. Ripe ovaries showed the presence of a wide size range of mature ova with indistinct minor modes within the group, thus manifesting fractional spawning within the season. Largest oocytes of 966 Î¼m in fully ripe condition appeared in April and October. High gonadosomatic index (GSI) values were encountered in October and April followed by a sudden drop in November and May. The males and females were found to mature at 115 and 118 mm respectively. Sex ratio showed skewness in some of the months. Overall sex ratio showed significant dominance of males and the mean ratio of males to females was 1:0.58.